Impact of high doses of 6% hydroxyethyl starch 130/0.42 and 4% gelatin on renal function in a pediatric animal model. Issue 3 (30th December 2015) - Witt, Lars; Glage, Silke; Lichtinghagen, Ralf; Pape, Lars; Boethig, Dietmar; Dennhardt, Nils; Heiderich, Sebastian; Leffler, Andreas; Sümpelmann, Robert
Summary: Objectives: Despite serious renal side effects in critically ill adult patients, artificial colloids are still fundamental components of perioperative fluid therapy in infants and children, although the impact of 6% hydroxyethyl starch (HES) and 4% gelatin (GEL) on renal function during pediatric surgery has not been identified yet. Aim: To determine the impact of high doses of artificial colloids on renal function, we conducted an experimental animal study and hypothesized that neither the infusion of HES nor of GEL would have a serious impact on renal function. Methods: Fifteen sedated piglets were randomly assigned to receive an infusion of either 50 ml·kg −1 HES or GEL, or a balanced electrolyte solution (crystalloid group). Before and 1 week after infusion, serum and urine renal function tests were recorded and renal biopsies were taken. Results: Serum and urine renal function tests revealed no increase after administration of HES and GEL, and only a discrete increase in serum creatinine (median 9.8 μmol·l −1, 95% CI 4.0–19.1) in the crystalloid group. Histopathological examination indicated a sparsely, multifocal infiltration of mononuclear cells in all groups and an unspecific pyelectasia of one animal in the GEL group. Conclusions: After high doses of HES or GEL in piglets, no relevant impact on renal function could be found. These results confirm that AKI after HES or GEL is very unlikely in hemodynamically stable perioperative patients with normal renal function. Abstract :